2003
DOI: 10.1021/jf0262357
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoids Detection by HPLC-DAD-MS-MS in Lemon Juices from Sicilian Cultivars

Abstract: High-performance liquid chromatography-diode array detector (HPLC-DAD) coupled with electronspray mass spectrometry (ESI-MS) was used to detect the flavonoid profile in lemon juices obtained from the main Sicilian cultivars (Femminello comune, Monachello, and Interdonato). Significant amounts of an unusual constituent were found in the lemon juice of the above-mentioned cultivars together with eriocitrin, hesperidin, and diosmin. Following purification by preparative HPLC, the structure was assigned as 6,8-di-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
74
2
7

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(93 citation statements)
references
References 28 publications
9
74
2
7
Order By: Relevance
“…In three types of lemon juice, eriocitrin and hesperidin amounts were detected as 84-298 mg/L and 88-197 mg/L, respectively. Our hesperidin results were in harmony with the Caristi et al (2003) findings. However; other researchers indicated that eriocitrin (eriodictyol 7-O-β-rutinoside) was the main flavonoid in lemon fruit (Tripoli et al 2007;Miyake et al 2006).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…In three types of lemon juice, eriocitrin and hesperidin amounts were detected as 84-298 mg/L and 88-197 mg/L, respectively. Our hesperidin results were in harmony with the Caristi et al (2003) findings. However; other researchers indicated that eriocitrin (eriodictyol 7-O-β-rutinoside) was the main flavonoid in lemon fruit (Tripoli et al 2007;Miyake et al 2006).…”
Section: Resultssupporting
confidence: 89%
“…Similarly, Gattuso et al (2007) reported that lemon juice is characterized by the presence of significant amounts of the flavanones, hesperidin (20.5 mg/100 mL) and eriocitrin (16.7 mg/100 mL). Caristi et al (2003) studied on the flavonoid profile in lemon juices obtained from the main Sicilian cultivars (Femminello comune, Monachello and Interdonato). In three types of lemon juice, eriocitrin and hesperidin amounts were detected as 84-298 mg/L and 88-197 mg/L, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The oil pulp can therefore be used as a protein source, and the root be used to produce acridine. Currently, there are many studies that examine the structure and function of natural source phenolic and flavonoid compounds, as well as their antioxidant, anticancer roles in noncommunicable diseases 13,14 .…”
Section: Introductionmentioning
confidence: 99%
“…In China, the leaves of S. matsudana were used as a kind of tea. In our previous investigation, its extract exhibited strong anti-obesity activity [5][6][7]. Flavonoids as anti-obesity compounds were isolated in this plant [8,9].…”
Section: Introductionmentioning
confidence: 88%